An Analysis of Staff Perceptions on Translanguaging in Teaching and Learning at One South African University - Mpofu, Tarisai; Ndebele, Clever (Research in Social Sciences and Technology, 2025)
Translanguaging is increasingly recognized as an essential strategy to improve epistemic access in multilingual societies, including many developing societies. This view is especially spurred by scholarly results that have confirmed that all languages are essential resources for learning beyond the language of teaching and learning. Therefore, this study focused on the perceptions of academics at a South African University on translanguaging, as they are crucial in successfully implementing these strategies to improve learning. The study employed a mixed-methods approach, using semi-structured questionnaires to gather academic data. Descriptive statistics were used to analyse the quantitative data, while the qualitative data was analysed thematically. The results show that most staff had positive perceptions of translanguaging and conceded that it positively affected student learning. However, a few noted that using other languages was an impediment since students do not understand all languages. The study recommends that universities provide academics with language learning opportunities, ensure that academics understand the official university language policies, and provide training on translanguaging to ensure that academics know translanguaging strategies that can be adopted in university learning spaces.